PENGARUH LINGKUNGAN ASRAMA TERHADAP PRESTASI BELAJAR SISWA KELAS IV MADRASAH IBTIDAIYAH SWASTA MA’HAD AL-ZAYTUN - Amelia Muasyasya; Dede Indra Setiabudi; Irvan Iswandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship and influence of the dormitory environment on the learning achievement of fourth-grade students at Madrasah Ibtidaiyah Swasta Ma'had Al-Zaytun. A conducive learning environment is a crucial factor in educational success, and the boarding school system is believed to contribute positively to students' academic achievements through strict supervision, regular schedules, and controlled supporting facilities. This research employs a quantitative approach with a population of all fourth-grade students at MI Swasta Ma'had Al-Zaytun, totaling 158 students. A sample of 37 students was selected using purposive sampling based on criteria such as having lived in the dormitory for at least one semester and exhibiting a variety of learning achievement levels. Data was collected using a five-point Likert scale questionnaire to measure students' perceptions of the dormitory environment and learning achievements, which were tested for validity and reliability. Data analysis used Pearson Product Moment correlation and simple linear regression tests. The results showed a weak negative relationship between the dormitory environment and students' learning achievements, with a correlation coefficient of -0.318 (p = 0.055). This relationship is not significant at the 5% significance level, although it approaches significance at the 10% level. Regression analysis indicates a negative influence of the dormitory environment on learning achievement with a regression coefficient of -0.203 and an R Square value of 0.101, meaning the dormitory environment explains only 10.1% of the variation in learning achievement, while the remaining 89.9% is influenced by other factors such as study motivation, teaching methods, family support, and students' physical condition. Keywords: Dormitory Environment, Learning Achievement, Madrasah Ibtidaiyah